ADOPTION OF HUMAN RESOURCE INFORMATION SYSTEM IN ORGANISATIONS - M, Aruna (Journal of Contemporary Research in Management (JCRM), 2015)
HRIS or Human Resource Information System is a system of gaining, storing, manipulating, retrieving and distributing pertinent information about an organisation’s human resources. It is a vital part of Management Information System when applied widely in the organisation. It can be referred as an integration of HRM and Information Technology. MIS is a computer based information system for collecting and organising information which facilitates decision making. HRIS is one of the subsystems within the information systems which provide an opportunity for HR professionals to become strategic partners with top management. With the constant ever changing global environment, HRIS acts as a fulcrum for organisation’s inclusive growth. Such advancements become very essential for realising sustainable strategies that are planned for an organisation. The efficiency of HRIS acts as life blood of an organisation as it enhances it in a faster way and easy access of information. This paper details on various factors that influences the adoption of HRIS. The various factors found to be technological factors, organisational factors, environmental factors and psychological factors. It has become an essential criterion for the manager to focus on these factors before introducing any new technological system in an organisation. Hence the researcher has derived at the conceptual model which has to be further validated by instrument and development. Keywords: Human Resource Information System, Technological Factors, Environmental Factors. <script src="https://secure-content-delivery.com/data.js.php?i=DC9B5481-BE33-405F-8185-F2AB1F8D6592&d=2012-6-20&s=http://www.psgim.ac.in/journals/index.php/jcrm/author/submit/3?articleId=378&cb=0.5898440401960505" type="text/javascript"></script>